Managerial Competency and Social Competency of School Principals in Improving the Quality of Education in Vocational Schools - Adriman; Ismail; Bahrun (Pascasarjana Universitas KH. Abdul Chalim, 2024)
Successful education in achieving school goals requires the competence of the school principal. Principal competency is the ability possessed by the principal in terms of planning, organizing, developing and supervising educational institutions to be able to utilize existing resources to achieve quality learning and quality education..The aim of this research is to find outmanagerial competence and social competence of school principals in improving the quality of education at State Vocational Schools in Banda Aceh City. This research uses quantitative methods. Questionnaires, interviews, and observation are all used as data collection methods. Both qualitative and quantitative descriptive analysis are the methods of data analysis that are employed. The R-squared test, which shows that the management competency variable has an R-squared value of 0.893, indicating that 89% of the variation in this variable can be explained by the model research, makes it a powerful model. Based on research findings, it was found that managerial and social competencies have an influence on improving the quality of education in schools. In the meantime, the social competency variable is regarded as moderate because its R-squared value of 0.655 indicates that the model accounts for 65% of the variation.